Desmopressin versus Oxybutynin for Nocturnal Enuresis in Children in Bandar Abbas: A Randomized Clinical Trial - Ghasemi, Kambiz (Electron Physician, 2016)
BACKGROUND: Nocturnal enuresis is among the most common disorders in children. Several pharmacological and non-pharmacological treatments are available for nocturnal enuresis. Studies for reaching the best pharmacological treatment for this disorder are continuing. OBJECTIVE: To compare the effectiveness and safety of Desmopressin and oxybutynin for treatment of nocturnal enuresis in children from Bandar Abbas in 2014. METHODS: This randomized controlled trial was conducted in 2014 and participants included 66 children with nocturnal enuresis who were more than 5 years old. Patients were randomly assigned into two groups. The first group received 120 microgram Desmopressin daily for 2 months, then 60 microgram daily for 2 months, then 60 microgram every 2 days. The second group received 5 mg oxybutynin twice a day for 6 months. The patients were followed after 1, 3, and 6 months to track treatment response. The study outcomes were frequency of nocturnal enuresis, urinary incontinency, urgency, and frequency. Data were analyzed using SPSS software. RESULTS: There were no significant differences between the two groups with respects to sex, age, place of residence, and parents’ education (p<0.05). Nocturnal enuresis, incontinency, urgency, and frequency of nocturnal enuresis was significantly lower with Desmopressin treatment in comparison to the oxybutynin treated group after 1 and 3 months (p<0.05). In addition, constipation and xerostomia were more frequent among the oxybutynin group after 1, 3, and 6 months (p<0.01). Blurred vision was also more frequent among oxybutynin group after 3 months (p<0.01). After 6 months the frequency of nocturnal enuresis and its frequency was higher in oxybutynin group in comparison to the Desmopressin group (p<0.05). CONCLUSION: Desmopressin is more effective and has lower rate of side effects in comparison to oxybutynin for treatment of nocturnal enuresis. We recommend using Desmopressin for treatment of nocturnal enuresis in children. More studies are needed to achieve the best pharmacological treatment option for treatment of nocturnal enuresis. TRIAL REGISTRATION: The trial is registered at ClinicalTrials.gov with a ClinicalTrials.gov Identifier: NCT02538302 FUNDING: The funder of this research is Hormozgan University of Medical Sciences.